Homology modeling of Leishmania donovani enolase and its molecular interaction with novel inhibitors - Jay Prakash Mahato; Sindhuprava Rana; Maneesh Kumar; Surendra Sarsaiya (Wolters Kluwer Medknow Publications, 2017)
Introduction: The treatment of Indian tropical disease such as kala-azar is likely to be troublesome to the clinicians as AmpB- and miltefosine-resistant Leishmania donovani has been reported. The rationale behind designed a novel inhibitors of model of L. donovani enolase and performing a binding study with its inhibitors to gain details of the interaction between protein residues and ligand molecules. Methods and Materials: The L. donovani enolase model consists of two typical domains. The N-terminal one contains three-stranded antiparallel β-sheets, followed by six α-helices. The C-terminal domain composes of eleven-stranded mixed α/β-barrel with connectivity. The first α-helix within the C-terminal domain, H7, and the second β-strand, S7, of the barrel domain was arranged in an antiparallel fashion compared to all other α-helices and β-strands. The root-mean-square deviation between predicted model and template is 0.4 Å. The overall conformation of L. donovani enolase model is similar to those of Trypanosoma cruzi enolase and Streptococcus pneumoniae enolase crystal structures. Result: The key amino acid residues within the docking complex model involved in the interaction between model enolase structure and ligand molecule are Lys70, Asn165, Ala168, Asp17, and Asn213. Conclusion: Our theoretical prediction may lead to the establishment of prophylactic and therapeutic approaches for the treatment of kala-azar. This biomedical informatics analysis will help us to combat future kala-azar.